2010
DOI: 10.1002/app.33261
|View full text |Cite
|
Sign up to set email alerts
|

Surface preparation for adhesive bonding of polycyanurate‐based fiber‐reinforced composites using atmospheric plasma treatment

Abstract: In this article, the effects of atmospheric plasma treatment on the microstructural, chemical, and mechanical behavior of epoxy-bonded polycyanurate composites are investigated. Adhesive bond strength of plasma-treated specimens exhibited strength increases of over 35% to that of peel-ply and solvent-wiped surface preparation techniques. The improvements were as much as 50% greater than those obtained using abrasive surface preparation techniques. X-ray photoelectron spectroscopy analysis showed an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…As duration exposure increases, an increase in surface oxygen levels is also observed. These results agree with previous studies [11][12][13][14][15]. However, previous investigations have also shown that the as-treated oxygen levels may not necessarily represent the functional groups participating in the chemical bonding between the treated surface and the epoxy infiltrate.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As duration exposure increases, an increase in surface oxygen levels is also observed. These results agree with previous studies [11][12][13][14][15]. However, previous investigations have also shown that the as-treated oxygen levels may not necessarily represent the functional groups participating in the chemical bonding between the treated surface and the epoxy infiltrate.…”
Section: Resultssupporting
confidence: 91%
“…However, numerous studies have shown that adhesives do not typically bond well to thermoplastics resins used in 3D printing, reducing their ability to transfer stress and achieve strong bonds for efficient utilization [11,12]. Plasma treatment has been shown to improve bonding in a number of polymer systems as well as a few structural composites materials systems with promising results [13,14]. The plasma can activate a species such as oxygen gas forming a highly reactive atomic oxygen free radical.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the surface roughness contributed little benefit to the lap-shear strength and was not the primary reason for the increase in the lap-shear strength of APPT-treated SMC joints. On the contrary, the change of chemical properties had an important effect on the increase in the lap-shear strength, which agrees with the viewpoint of Zaldivar et al [35] and Schafer et al [36]. In particular, the hydroxyl and carboxyl groups increased significantly after APPT and may be the primary reason for the improvement in the lap-shear strengths of APPT-treated SMC joints.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, thermoplastic composites, which are inherently difficult to adhesive bond, require long cure processing, and only a low strength bond can be obtained. Moreover, adhesive bonding requires surface treatment before joining, which is very expensive [14][15][16][17][18][19]. Recently, many innovative joining technologies have been investigated, such as friction spot welding [20], resistance welding with inserted conductive elements [21,22], ultrasonically welding [23], and laser joining [24,25].…”
Section: Introductionmentioning
confidence: 99%